A utilização da infografia no ciberjornalismo de ciência e tecnologia: a perspetiva de quarto jornais nacionais - Pereira, Filipa (2015)
This communication aims to report a part of a research project focused on understanding the role of infographics as a facilitator of news content about science and technology. Are disclosed in this communication the results obtained from the analysis of infographics science and technology published in four national newspapers ("Jornal de Notícias"; "Público"; "iOnline" e "Expresso"). The work presented analyses the publishing of infographics according to the characteristics identified by some authors considered at the investigation theoretical approach. It is a preliminary work, however, behind the level of the relevant amount and dynamics of disclosure and publication of infographics science and technology in the four papers presented information.